Time Since Last Dental Clinic Visit and Self-Reported Health among the Elderly - Dong, Frank; Jacobson, Lisette T; Parsons, Susan; Ablah, Elizabeth (Kansas Journal of Medicine, 2013)
Background. This study determined the association between time since last dental clinic visit and self-reported health among the elderly (age ≥ 65 years). Methods. Data were from the 2010 Behavioral Risk Factor Surveillance System. A logistic regression analysis was conducted to identify factors that affect the self-reported general health of the elderly. Additionally, a negative binomial regression analysis was conducted to explore the association of time since last dental clinic visit and the self-reported number of physically unhealthy, mentally unhealthy, and sad days during the past 30 days. Results. Six predictors were identified affecting the self-reported general health of the elderly. Respondents were more likely to self-report “good, very good, or excellent” general health if they: visited the dental clinic within the past year, were non-Hispanic, had healthcare coverage, had fewer permanent teeth removed, received better education and were younger. A larger lapse of time since respondents’ last dental clinic visits was associated with increased number of mentally and physically unhealthy days and an increased number of sad days during the past 30 days. Conclusions. The positive association between better general health, fewer mentally and physically unhealthy days, and fewer sad days during the past 30 days and shorter periods of time between dental visits warrants further investigation to determine a possible causal relationship between overall health and dental visits.